2016
DOI: 10.1371/journal.pone.0154330
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the Transcription Factors Involved in Citrus Fruit Ripening from the Transcriptomes of a Late-Ripening Sweet Orange Mutant and Its Wild Type

Abstract: Fruit ripening is a genetically programmed process. Transcription factors (TFs) play key roles in plant development and ripening by temporarily and spatially regulating the transcription of their target genes. In this study, a total of 159 TFs were identified from a spontaneous late-ripening mutant 'Fengwan' (C. sinensis L. Osbeck) sweet orange (MT) and its wild-type counterpart ('Fengjie 72–1', WT) along the ripening period via the Transcription Factor Prediction of PlantTFDB 3.0. Fifty-two differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…Pêra during the sampling period (maximum size and weight of 43 mm diameter and 36.5 g, respectively) was similar to the data obtained by Araujo (2010) for fruits of the cultivar Valencia. As expected, based on the expression of Dof transcripts in sweet orange and other fruit species (Cai et al, 2013;Feng et al, 2016, Wu et al, 2016b, the CsDof genes analyzed showed different mRNA levels during the early stages of sweet orange fruit development analyzed here ( Figure 6). Expression of CsDof17 transcripts was the highest at all stages analyzed, indicating that this gene probably plays an important role in the development of sweet orange fruits.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Pêra during the sampling period (maximum size and weight of 43 mm diameter and 36.5 g, respectively) was similar to the data obtained by Araujo (2010) for fruits of the cultivar Valencia. As expected, based on the expression of Dof transcripts in sweet orange and other fruit species (Cai et al, 2013;Feng et al, 2016, Wu et al, 2016b, the CsDof genes analyzed showed different mRNA levels during the early stages of sweet orange fruit development analyzed here ( Figure 6). Expression of CsDof17 transcripts was the highest at all stages analyzed, indicating that this gene probably plays an important role in the development of sweet orange fruits.…”
Section: Discussionsupporting
confidence: 79%
“…In the case of CsDof9, we detected a further decrease in its mRNA expression as fruit ripening progressed. It is interesting to mention that CsDof9 (orange1.1g025998m) was found to be significantly down-regulated in a bud late-ripening mutant in comparison with its wild-type counterpart (Fengjie 72-1') during a later sampling period (150 -240 DAF) than the one used in this work (Wu et al, 2016b).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations